DIVERSITY OF CAPSICUM IN GEGERUNG VILLAGE, WEST LOMBOK - Fathul Muin; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Lombok is one of the islands in the Lesser Sunda Islands, home to a rich biodiversity, including plants. This research is necessary to determine the diversity of Capsicum plants in Gegerung Village. Research shows that two Capsicum species are present in Gegerung Village: Capsicum anuum and C. frutescens.